Response of narrowband ultraviolet-B phototherapy in pityriasis lichenoides-like mycosis fungoides: a case report - Silvia Rakhmadani; Kirantri Larasati; Flandiana Yogianti; Arief Budiyanto; Ardisa Pramudita; Paranita Ferronika (Published by Universitas Gadjah Mada, 2026)
Mycosis fungoides (MF) is a cutaneous T-cell lymphoma that often mimics other dermatological conditions, particularly in early stages. One rare subtype is pityriasis lichenoides-like mycosis fungoides (PL-like MF), which clinically resembles pityriasis lichenoides but demonstrates the histopathological features of MF, sometimes with overlapping characteristics. The management of MF varies according to disease stage, with skin-directed therapies, including narrowband ultraviolet B (NB-UVB) phototherapy, frequently used in early stages. A case is reported of a 28-year-old woman who presented with papules and erythematous patches on the trunk, arms, and legs that had worsened over two years. Histopathological examination of the skin biopsy confirmed PL-like MF. Initial treatment with topical corticosteroids for two months resulted in suboptimal improvement. The patient subsequently underwent 37 sessions of NB-UVB phototherapy with a cumulative dose of 58,764 mJ/cm². Pityriasis lichenoides-like MF is a rare variant of MF that poses diagnostic challenges. The management of MF is tailored to the disease stages. In early stages, skin-directed therapies (SDTs) are preferred, whereas in advanced or refractory MF, systemic therapy combined with SDTs is required. Narrowband UVB phototherapy is considered a safe and effective therapeutic option for early-stage MF, with mechanisms involving immunomodulation and induction of apoptosis in atypical lymphocytes. In this case, the patient demonstrated 87% clinical improvement following NB-UVB therapy, consistent with reports. Long-term follow-up is necessary to assess sustained remission and potential relapse.